(untitled) (Modern American Journal of Social Sciences and Humanities, 2026)
This article examines the interrelations between the categories of morality and the concept of belief in the context of humanities education. Morality is interpreted as a system of values, norms, principles, and evaluative categories that regulate human behavior, while belief is considered a stable inner conviction that gives personal meaning to moral choice and social responsibility. The study emphasizes that moral categories such as goodness, justice, duty, conscience, honor, responsibility, and dignity acquire practical significance when they are internalized through belief. At the same time, belief becomes socially and pedagogically valuable when it is guided by moral awareness and ethical reflection. The article argues that the relationship between morality and belief is not limited to theoretical philosophy, but is also important for the formation of students’ worldview, civic consciousness, and spiritual maturity. In pedagogical education, this relationship helps future specialists understand the ethical foundations of professional activity and interpersonal communication. The findings suggest that the integration of moral education, reflective dialogue, value-based learning, and humanitarian analysis can strengthen students’ ability to make responsible decisions and develop a conscious attitude toward personal and social values.